When Video Improves Learning in Higher Education - Sven Trenholm; Fernando Marmolejo-Ramos (Education Sciences, 2024)
The use of video in education has become ubiquitous as technological developments have markedly improved the ability and facility to create, deliver, and view videos. The concomitant pedagogical transformation has created a sense of urgency regarding how video may be used to advance learning. Initial reviews have suggested only limited potential for the use of video in higher education. More recently, a systematic review of studies on the effect of video use on learning in higher education, published in the journal Review of Educational Research, found, overall, effects to be positive. In the present paper, we critique this study. We reveal significant gaps in the study methodology and write-up and use a cognitive processing lens to critically assess and re-analyse study data. We found the results of this study to be only applicable to learning requiring lower-level cognitive processing and conclude, consistent with prior research, that claims of a universal benefit are not yet warranted.